Production and economics of carp polyculture in ponds stocked with wild and hatchery produced seeds - Md. Rafiqual Islam Khan; Md. Taskin Parvez; Mohammad Golam Sarowar Talukder; Md. Akhtar Hossain; Md. Shamsul Karim (Journal of Fisheries, 2018)
Lack of quality carp seeds is one of the major problems for fish production in Bangladesh. This experiment was conducted during July to December 2013 to study the production and economics of carp polyculture using wild and hatchery produced seeds in ponds in Faridpur district, Bangladesh.  Seeds of native major carps (NMCs) (Catla catla, Labeo rohita and Cirrhinus mrigala) and non-native carps (NNCs) (Hypophthalmichthys molitrix, Ctenophryngodon idella, Aristichthys nobilis and Cyprinus carpio) from four different sources were tested in feed and fertilizer based polyculture ponds under controlled mesocosm trials with four treatments (T1–T4), each with four replications. Combination, weight and density of the stocked species were same for all the treatments. Water quality parameters were monitored monthly and mean values were found within suitable range for fish farming. Mean final weight, weight gain, specific growth rate and yield of L. rohita, C. catla and C. mrigala were found significantly (P < 0.05) higher with treatment T1, T3 and T2 respectively. Treatments T1-T3 varied more significantly (P < 0.05) than treatment T4 for total fish yield and cost benefit ratio.  Polyculture of wild sourced NMCs and hatchery produced NNCs were found more profitable than aquaculture of hatchery produced NMCs and NNCs.